Monetary policy and economic growth during the Covid-19 pandemic: ASEAN-5 and China - Zhang, Zhe (2024)
This study examines the effectiveness of monetary policy during the Covid-19 pandemic in China and five ASEAN countries by analyzing data from 2019Q1 to 2022Q4, the study utilizes the Autoregressive Distributed Lag (ARDL) model to evaluate the short and long-term impacts of monetary policy on the economic growth of the selected countries. The results demonstrate that expansionary monetary policy has a significant impact on economic stability during the pandemic, with overnight policy rates and money supply being the primary monetary instruments. Furthermore, the study reveals that inflation and exchange rates play a crucial role in stabilizing the economy both in the short and long run during the Covid-19 crisis period. The study also considers the impact of the World Uncertainty Index, as recommended by the International Monetary Fund, this index captures uncertainty related to political and economic events and represent a good insight of major economic and political issues happens during covid-19 time period. These findings have important implications for policymakers, suggesting that an appropriate environment is necessary to restore the confidence of both domestic and foreign investors and ensure economic stability. The study highlights the need for the monetary authorities to develop crisis management plans to address unforeseen circumstances, especially during crisis times, and emphasizes the importance of continuing research on the impact of monetary policy during these periods.